Effect of sheep placenta extract on D-galactose-induced aging mouse - He, Shan; Wu, Yue; Lu, Kaixian; Zhu, Heng; Wang, Xuan; Qin, Yaoyao; Li, Huan; Zeng, Lin; Han, Jiaojiao; Zhou, Xiangyang; Zhang, Bin; Tang, Bo (Frontiers in Pharmacology, 2025)
IntroductionSheep placenta extract (SPE) is a representative traditional medicinal substance that exhibits multiple experimentally validated physiological properties, including anti-aging effects, wound healing acceleration, antioxidant activity, and anti-inflammatory mechanisms. However, the mechanism by which SPE influences the delay of aging is still not yet clear.MethodsExploring the effects of sheep placenta extract on D-gal induced senescence in a mouse model of aging by macrogenomics and metabolomics.ResultsIn the serum of aging mice treated with SPE, the levels of antioxidant function such as superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) were notably higher compared to those in the blank group, whereas malondialdehyde (MDA) levels decreased. We revealed that SPE alleviated the changes in gut microbiota caused by aging in mice, with a significant decrease in the Firmicutes/Bacteroidetes (F/B) ratio in the gut. Furthermore, Akkermansia muciniphila (A. muciniphila), which is known for its regulating immune response and potential anti-aging effects, showed a significant increase of 1177.94%. The analysis of UHPLC-QE-MS combined with orthogonal partial least squares discriminant analysis (OPLS-DA) screening of differential metabolites in mouse serum metabolic profiles revealed a significant upregulation of cis-5,8,11,14,17-eicosapentaenoic acid (EPA) and triptolide in serum metabolites, following SPE treatment, which are commonly believed to have immunosuppressive, anti-inflammatory, anti-proliferative, and anti-tumor effects.DiscussionThe role of SPE in ameliorating aging may be associated with the increased abundance of A. muciniphila in the gut microbiota and the accumulation of two metabolites, EPA and triptolide, in the serum.